굴포천 유역 내 수질 및 퇴적물의 오염물질 특성 파악에 관한 연구 - 안태웅(Tae Woong Ahn); 정재훈(Jae Hoon Jung); 김태훈(Tae Hoon Kim); 김세원(Sea Won Kim); 최이송(I Song Choi); 오종민(Jong Min Oh) (Daehan hwan'gyeong gonghag hoeji, 2012)
The water quality of Gul-po Stream, the subject of this study, has been deteriorating because of the inflow of domestic sewage and the industrial wastewater due to industrialization and the problems relating to the structure of river including slow flow rate and the covering of river. In particular, the domestic sewage from small-medium sized factories by the river and large-scale industrial complex by the upper and middle streams of the river, and the domestic sewage from increasing population due to the regional development are the main pollution sources. Thus, this study aims to survey the water quality and the sediment affecting Gul-po Stream; monitor the state of pollution in water body; assess the yield of sediment and investigate the water quality of river and the problems arising from sediment; and then suggest reasonable ways to improve the situation. The findings from surveying pollution load shows the discharge increases up to average 72.8 times from the upper stream to the downstream of Gul-po Stream, and pollution load increases up to: SS 111 times, BOD 150 times, COD 145 times, the nutrient T-N 222 times and T-P 312 times on an average basis. As for the pollution concentration range, ignition loss is 1.29~12.43%; COD is 4,015~37,547 kg/day; T-N and T-P 94.8~352.5 kg/day and 81.8~372.3 kg/day, respectively. As for the releasing rate of sediment, T-N is -14.46~$156.61mg/m^2/day$; T-P is -11.53~$26.10mg/m^2/day$, indicating the likelihood of internal contamination due to the elution of sediment. This study is expected to be used as basic data to manage Gul-po Stream basin. 본 연구의 대상지인 굴포천은 산업화와 도시화로 인한 생활하수 및 공장폐수의 유입, 느린 유속과 하천 복개 등과 같은 유입오염원과 하천 구조적 문제로 인하여 수질이 악화되어 왔다. 특히 하천변의 소규모 영세 공장, 중 상류에 형성된 대규모 공업단지, 지역개발에 따른 인구증가로 인한 생활하수 등은 굴포천의 주오염원이다. 따라서 본 연구에서는 굴포천에 영향을 주는 다양한 수질 및 퇴적물의 오염원에 대하여 조사하고, 수체내에서의 오염현황을 모니터링하며, 퇴적물의 용출량을 평가하고 하천의 수질 및 퇴적물의 문제점 파악을 통한 합리적인 개선방향을 제시하고자 한다. 본 연구에서 오염부하량 조사결과, 굴포천 상류에서 하류로 향할수록 유량은 평균 72.8배 증가하였으며, 오염부하량은 평균 SS 111배, BOD 150배, COD 145배, T-N 222배, T-P 312배의 오염부하가 증가함을 알 수 있었다. 퇴적물의 오염 농도 범위는 강열감량의 경우 1.29~12.43%, COD는 4,015~37,547 kg/day의 범위로 나타냈다. 영양물질인 T-N, T-P는 각각 94.8~352.5 kg/day, 81.8~372.3 kg/day의 범위를 나타냈다. 퇴적물의 용출속도의 경우, T-N은 -14.46~$156.61mg/m^2/day$의 용출속도를 보였으며, T-P의 경우 -11.53~$26.10mg/m^2/day$의 용출속도를 보임으로서 퇴적물 용출에 의한 내부오염의 가능성이 있음이 나타났다. 본 연구의 결과를 통해 굴포천 유역을 효율적으로 관리하는데 기초자료로 활용할 수 있을 것으로 사료된다.